Synthesis of imidazole and chalcones - Izzuddin Mohd. Idris, 1994-, author; Joazaizulfazli Jamalis, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2018